SOCIAL REHABILITATION: INTERVENTION OF SOCIAL WORKERS IN THE UNINHABITABLE HOUSING PROGRAM IN THE CITY OF BANDUNG - Willya Achmad (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
Home rehabilitation programs aim to improve the quality of life for people living in inadequate housing conditions. However, the success of these programs often depends on the support and intervention of social workers in planning, implementing and monitoring the rehabilitation process and its impact on the communities involved. This study aims to analyze the role and effectiveness of the social worker's intervention in the rehabilitation program for uninhabitable houses in the city of Bandung. This research method uses a qualitative approach with descriptive analysis. This research reveals that the Social Rehabilitation Program for Uninhabitable Houses (RS-RTLH) in the city of Bandung has succeeded in overcoming the problem of poverty and improving the quality of housing for the poor. During the period from 2018 to 2021, this program succeeded in rehabilitating a total of 8,306 uninhabitable housing units . Despite facing challenges such as complex communication factors, limited human resources, and bureaucratic dynamics, social worker interventions play an important role in bridging information gaps, assisting in planning appropriate interventions, and providing ongoing evaluation assistance. The social worker's approach in making contact, assessing, compiling work programs, mentoring, and terminating plays a role in ensuring that this program provides optimal results, reduces social dependency, and improves the welfare of the people being assisted.